1991
DOI: 10.1001/jama.265.13.1715
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of tuberculosis among North Carolina migrant farm workers

Abstract: Although tuberculosis (TB) has been recognized as a significant health problem of migrant farm workers, the nature and extent of the problem have been poorly defined. We report the first population-based study of TB in a random sample of farm workers (n = 543) and the first use of recall antigens in an epidemiologic study of TB. Purified protein derivative positivity ranged from 33% in Hispanics to 54% in US-born blacks and 76% in Haitians. Active tubercular disease occurred in 3.6% of US-born blacks and 0.47%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…At the same time, farmworkers are at substantially greater risk than the general population for exposure to occupational injuries, communicable diseases (e.g., tuberculosis and HIV/AIDS), and dental diseases. [18][19][20][21][22][23][24][25][26] There is great concern about occupational exposure of farmworkers to agricultural chemicals and the short-and long-term effects of this exposure. [27][28][29][30] Farmworkers in North Carolina are overwhelming minority-group members, composed almost exclusively of Hispanic and African American workers.…”
Section: Case Study: Enhancing the Participation Of North Carolina Famentioning
confidence: 99%
“…At the same time, farmworkers are at substantially greater risk than the general population for exposure to occupational injuries, communicable diseases (e.g., tuberculosis and HIV/AIDS), and dental diseases. [18][19][20][21][22][23][24][25][26] There is great concern about occupational exposure of farmworkers to agricultural chemicals and the short-and long-term effects of this exposure. [27][28][29][30] Farmworkers in North Carolina are overwhelming minority-group members, composed almost exclusively of Hispanic and African American workers.…”
Section: Case Study: Enhancing the Participation Of North Carolina Famentioning
confidence: 99%
“…41 More recently, a study of migrant farm workers in North Carolina found that 33% of Latino workers were TST-positive. 19 In our study, several findings, including the remarkably high rate of tuberculin positivity among workers from higher-prevalence TB countries (80.6%), the 100% rate of positivity among workers on the same custodial crew, and the 70% rate of positivity among individuals riding in the same car, argue that workplace transmission occurred.…”
Section: Discussionmentioning
confidence: 49%
“…16 TB outbreaks among migrant farm workers have also been documented, and the Advisory Council for Elimination of Tuberculosis (ACET) has cited overcrowded living conditions, generally poor access to health care, and the presence of complex medical problems among workers who have emigrated from higher-prevalence TB regions as risk factors. [17][18][19][20][21][22] Few reports document TB transmission in industrial workplaces, particularly among workforces with significant numbers of foreign-born employees. In a 1986 study of a Vermont furniture factory with "good" ventilation, the rate of tuberculin skin test (TST) positivity was higher in the department where an active case had worked.…”
mentioning
confidence: 99%
“…19 The incidence in African-American migrant workers is nearly 3000 times that of the national average. 15 In industrialized countries, cases of tuberculosis are not uncommon; however, isolated M. tuberculosis infection of the CNS is rare, 17 since cases of CNS-TB are most commonly found in association with an infection in another organ system or with miliary tuberculosis. 28 In 1979, there were 4000 reported cases of extrapulmonary tuberculosis in the United States, of which approximately 600 were cases of meningitis, 26 which is a dramatic rise in the number of reported cases of CNS-TB.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of tuberculosis in these individuals is up to 3000 times the rate seen in the general population. 8,11,12,15,19,20,27 Few cases of M. tuberculosis CNS infection have been reported in the United States; it is estimated that 15% of these 4000 yearly cases of extrapulmonary tuberculosis involve the brain or spinal cord. 25 Most of these are cases of meningoencephalitis or a spinal column disease; however, a rare case of intracranial tuberculoma may be seen during treatment of tuberculous meningitis.…”
mentioning
confidence: 99%